Alveolar Soft Part Sarcoma: A Single-Center 26-Patient Case Series and Review of the Literature. (15th May 2012) - Ogura, Koichi; Beppu, Yasuo; Chuman, Hirokazu; Yoshida, Akihiko; Yamamoto, Noboru; Sumi, Minako; Kawano, Hirotaka; Kawai, Akira
Abstract : Background. Alveolar soft part sarcoma (ASPS) is a rare tumor, and little information is available regarding its clinical features and appropriate treatments. Methods. A retrospective review of 26 consecutive ASPS patients (12 male, 14 female; mean age of 27 years) treated at our institution over 30 years (mean followup; 71 months) was performed. Results. The primary tumor developed in the lower extremity (12), trunk (8), and upper extremity (6), with an average size of 7.2 cm (range, 2–14 cm). The AJCC stage at presentation was IIA (7), III (3), and IV (16). Surgical excision was performed in 20 patients (R0 18, R1 plus radiotherapy 2) without local recurrence. Six patients (stage IIA 3/7, stage III 3/3) later developed metastases after an average period of 28.7 months. The median survival of the 26 patients was 90 months, with overall 5/10-year survival rates of 64%/48%. AJCC stage and tumor size were significant prognostic factors. Significant palliation and slowing of metastasis progression were achieved with gamma knife radiotherapy. Nine patients receiving chemotherapy showed no objective response. Conclusions. ASPS is indolent but has a high propensity for metastasis. Early diagnosis and complete excision of the small primary tumor are essential in the treatment of ASPS.